2004
DOI: 10.1001/jama.291.4.470
|View full text |Cite
|
Sign up to set email alerts
|

Communication of Randomization in Childhood Leukemia Trials

Abstract: Context Most children diagnosed as having leukemia become research subjects in randomized clinical trials (RCTs), but little is known about how randomization is explained to or understood by parents. Objective To investigate physicians' explanation and parental understanding of randomization in childhood leukemia RCTs. Design and Setting A multisite study of the informed consent communication process for RCTs of childhood leukemia. Consecutive cases were recruited from pediatric oncology inpatient wards at 6 U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
172
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(175 citation statements)
references
References 32 publications
2
172
1
Order By: Relevance
“…Structuring the diagnostic meeting in a manner that simplifies the presentation of information and confirms understanding is consistent with Kodish's work examining consent/assent procedures for phase I and III clinical trials. [35][36][37] This approach may allow AYAs to become involved in the decision-making process while providing caregivers with the opportunity to process information about cancer, treatment, and clinical trials. Decision tools [38][39][40] or strategies for improving the delivery of healthcare information and enhancing the decision-making process, used together with the PRPQ, may provide an effective method to addressing attitudes toward cancer clinical trials and engage, educate, and guide AYA decision-making for treatment via a phase III clinical trial.…”
Section: Barakat Et Almentioning
confidence: 99%
“…Structuring the diagnostic meeting in a manner that simplifies the presentation of information and confirms understanding is consistent with Kodish's work examining consent/assent procedures for phase I and III clinical trials. [35][36][37] This approach may allow AYAs to become involved in the decision-making process while providing caregivers with the opportunity to process information about cancer, treatment, and clinical trials. Decision tools [38][39][40] or strategies for improving the delivery of healthcare information and enhancing the decision-making process, used together with the PRPQ, may provide an effective method to addressing attitudes toward cancer clinical trials and engage, educate, and guide AYA decision-making for treatment via a phase III clinical trial.…”
Section: Barakat Et Almentioning
confidence: 99%
“…Research on parental voluntariness that incorporates objective measurement of the informed permission process and physician or researcher behaviors is also needed. For example, Kodish and colleagues 1,28 have conducted numerous studies related to informed permission in pediatric leukemia. In those studies they used an observer checklist that provides an objective assessment of elements of the protocol discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research related to parental permission* to research or treatment in pediatric settings has focused largely on disclosure and understanding [1][2][3] and motivations for agreeing to or declining research participation. 4,5 Little empirical attention has been paid to the voluntariness of such decisions.…”
mentioning
confidence: 99%
“…I have found that one important role that I have had in research with pediatric colleagues was to facilitate connections and collaborations with other researchers from other professional disciplines and/or psychologists with complementary specialized expertise. Examples from my own experience include involving an anthropologist to help understand the complex family context of failure to thrive and economic disadvantage (Drotar, 1991), engaging child development expertise to measure the information processing of young children with HIV infection , or helping to facilitate interdisciplinary teams that included oncology, nursing, anthropology, bioethics, and biostatistics (Kodish et al, 2004).…”
Section: Involving a Range Of Professional Disciplines In Collaboratimentioning
confidence: 99%